Mxene-iron-molybdenum bimetallic sulfide and carbon composite material as well as preparation method and application thereof
By preparing Mxene-ferromolybdenum bimetallic sulfide@carbon composite, the problem of poor conductivity and rate performance of metal sulfide negative electrode materials in sodium ion batteries is solved, the conductivity and rate capability of the battery is improved, and the comprehensiveness of the battery is improved. Performance and cycle stability.
Patent Information
- Application Number
- CN202411371361.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
AI Technical Summary
The conductivity and rate performance of metal sulfide negative electrode materials in sodium ion batteries affects the cycle life and electrochemical performance of the battery.
The nanosphere structure was prepared by hydrothermal reaction and high-temperature vulcanization treatment using Mxene-ferromolybdenum bimetallic sulfide@carbon composite material, and mixed with Mxene to form heterogeneous composite material to improve electron transport efficiency and mechanical stability.
It significantly improves the conductivity and magnification capabilities of the material, enhances the comprehensive performance of sodium ion batteries, reduces the volume expansion during charging and discharging, and shortens the particle diffusion path between the positive and negative electrodes.
Smart Images

Figure CN119240798A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a Mxene-iron-molybdenum bimetallic sulfide@carbon composite material and a preparation method and application thereof. Background Art
[0002] The rapid growth of the world's population and the rapid development of the global economy have led to severe problems in the production of fossil fuels, such as resource depletion and environmental pollution. The emergence of renewable energy such as solar energy, geothermal energy, wind energy, ocean energy and nuclear fusion energy has gradually changed the global energy consumption structure. However, intermittent renewable energy can only generate electricity under suitable conditions, and only by storing electricity from renewable energy can the electricity demand be continuously supplied.
[0003] As one of the main power sources for portable electronic devices, hybrid vehicles and electric vehicles, lithium-ion batteries have achieved great success. However, due to the limited resources and high prices of lithium, lithium batteries cannot meet the growing industrial demand. Because sodium resources are abundant and cheap, and sodium has similar physical and chemical properties to lithium, battery components, etc., people have once again focused on sodium-ion batteries. The larger radius of sodium ions relative to lithium ions leads to large resistance to sodium embedding / ejection in the positive and negative electrodes of the battery, poor reversibility, and large irreversible capacity loss. Therefore, it is urgent to develop new electrode materials to improve their electrochemical performance.
[0004] In-depth research on negative electrode materials shows that negative electrode materials can be divided into embedded type, alloy type, and conversion type according to different electrode reaction mechanisms. Embedded materials are mainly carbon-based materials, which have stable structures but low reversible capacity; alloy materials are mainly composed of elements of the fourth and fifth main groups, with high theoretical capacity, but their huge volume expansion limits their development. Conversion materials are mainly metal oxides and metal sulfide compounds. Due to their high theoretical specific capacity and abundant redox sites, they have higher capacity than embedded materials and more stable cycle performance than alloy materials. Therefore, conversion negative electrode materials are widely used in sodium ion batteries. The sodium storage mechanism of conversion materials is: metal oxides, sulfide compounds and sodium undergo redox reactions to produce a series of reactions, and finally generate metal elements and Na2X (X-sulfide elements). Among conversion materials, transition metal sulfides have higher conductivity and lower band gap than oxides, and the weaker MS bond relative to MO can provide faster reaction kinetics, which is beneficial to sodium storage. However, metal sulfides also have key issues that affect the cycle life of batteries, such as low electrical conductivity, large volume expansion, and the shuttling effect of polysulfides.
[0005] To solve the above problems, researchers have modified the negative electrode materials by means of material nano-sizing, metal ion doping, composite of multiple metal sulfides, and surface coating. The Chinese patent with publication number CN111628155A discloses a molybdenum-tin bimetallic sulfide negative electrode material for lithium-ion / sodium-ion batteries and its preparation method, including using tin oxalate microrods as a precursor, preparing tin dioxide microrods with a porous structure by simple heat treatment; adding a certain amount of ammonium molybdate, dopamine hydrochloride, ethanol and ammonia solution, stirring the reaction to obtain a composite precursor, and then sulfurizing the composite precursor under an inert atmosphere to obtain a rod-shaped SnS / MoS2@C composite material. Although the stability of the composite material prepared in this patent has been enhanced to a certain extent when used in electrodes, the conductivity and rate capability still need to be further improved. Summary of the invention
[0006] In view of the technical problems of poor electrical conductivity and rate performance of metal sulfide negative electrode materials, the present invention proposes a Mxene-iron-molybdenum bimetallic sulfide@carbon composite material and a preparation method and application thereof. The prepared Mxene-iron-molybdenum bimetallic sulfide@carbon composite material can effectively improve the electrical conductivity and rate capability of the material, thereby improving the comprehensive performance of sodium ion batteries.
[0007] In order to achieve the above object, the technical solution of the present invention is achieved as follows:
[0008] A method for preparing a Mxene-iron-molybdenum bimetallic sulfide@carbon composite material comprises the following steps:
[0009] (1) dissolving an iron source, a molybdenum source and a carbon source in a solvent to prepare a mixed solution, and then performing a hydrothermal reaction to obtain bimetallic oxide nanospheres;
[0010] (2) subjecting the bimetallic oxide nanospheres to high temperature sulfurization to obtain iron-molybdenum bimetallic sulfide@carbon;
[0011] (3) Mxene and iron-molybdenum bimetallic sulfide@carbon are mixed by ball milling to prepare Mxene-iron-molybdenum bimetallic sulfide@carbon composite material.
[0012] The iron source is ferric chloride and / or ferric nitrate; the molybdenum source is one or more of sodium molybdate, ammonium molybdate or ammonium heptamolybdate.
[0013] The carbon source is polyvinyl pyrrolidone or polydopamine, the concentration of the carbon source in the mixed solution is 0.01-0.5 g / ml, and the solvent is water.
[0014] The molar ratio of the iron source to the molybdenum source is (1-3): (1-3), and the concentration of the molybdenum source in the mixed solution is 0.01-0.1 mmol / ml.
[0015] The conditions of the hydrothermal reaction are: temperature 160-240° C., time 12-24 h.
[0016] The sulfur source used in the high-temperature vulcanization treatment is one or more of sublimated sulfur, thiourea or thioacetamide; the mass ratio of the bimetallic oxide nanospheres to the sulfur source is (0.01-1): (0.01-1).
[0017] The temperature of the high temperature vulcanization treatment is 200-700° C. and the time is 2-6 hours.
[0018] The mass ratio of the Mxene to the iron-molybdenum bimetallic sulfide@carbon is 1:(1-2).
[0019] A Mxene-iron-molybdenum bimetallic sulfide@carbon composite material is used as a negative electrode material for a sodium ion battery. The preparation method comprises the following steps: mixing the Mxene-iron-molybdenum bimetallic sulfide@carbon composite material, a conductive agent and a binder, then dissolving and mixing them uniformly to obtain a slurry, and uniformly coating the slurry on the surface of a current collector to obtain a negative electrode sheet for a sodium ion battery.
[0020] Beneficial effects of the present invention:
[0021] 1. The synthesis method used in the present invention has a short process, a simple process, and a uniform product morphology. The prepared Mxene-iron-molybdenum bimetallic sulfide composite material is a negative electrode material for sodium ion batteries, and the prepared Mxene-iron-molybdenum bimetallic sulfide composite material has a uniform and controllable morphology.
[0022] 2. The present invention, through reasonable structural design, can realize efficient electron transmission and provide more active sites for the Mxene-iron-molybdenum bimetallic sulfide composite material, which is conducive to the electrochemical reaction of the battery. Second, due to the heterogeneous composite structure of Mxene-bimetallic sulfide, the mechanical stability of the material can be enhanced, the volume expansion during the charge and discharge process can be effectively reduced, the particle diffusion path between the positive and negative electrodes can be shortened, and the reaction kinetics of the electrode can be improved. Third, the conductivity and rate capability of the material can be effectively improved, thereby improving the overall performance of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 Scanning electron microscope images of Mxene-iron-molybdenum bimetallic sulfide@carbon composites with different proportions.
[0025] Figure 2 This is the XRD spectrum of the Mxene-iron-molybdenum bimetallic sulfide@carbon composite material in Example 1.
[0026] Figure 3 Impedance diagram of Mxene-iron-molybdenum bimetallic sulfide@carbon composite as anode material for sodium ion batteries.
[0027] Figure 4 This is the charge and discharge curve of Mxene-iron-molybdenum bimetallic sulfide@carbon composite material as the negative electrode material of sodium ion battery.
[0028] Figure 5 This is the rate performance diagram of molybdenum disulfide, iron-molybdenum bimetallic sulfide@carbon, and Mxene-iron-molybdenum bimetallic sulfide@carbon composite materials. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] A Mxene-iron-molybdenum bimetallic sulfide@carbon composite material, the preparation method comprising the following steps:
[0032] Step 1: Preparation of iron-molybdenum bimetallic oxide nanospheres:
[0033] Weigh 2mmol of ferric nitrate and 3mmol of sodium molybdate and dissolve them in 30ml of deionized water respectively, stir them evenly and record them as solution A and solution B respectively; add solution A into solution B while stirring, add 2.5g of polyvinyl pyrrolidone after sufficient stirring, and continue stirring to obtain a mixed solution; transfer the mixed solution into a polytetrafluoroethylene reactor, react at 200°C for 24 hours, cool to room temperature after the reaction is completed, take out the material, wash it with deionized water and ethanol by centrifugation for multiple times, and dry it to obtain an iron-molybdenum bimetallic oxide nanosphere precursor;
[0034] Step 2: Preparation of iron-molybdenum bimetallic sulfide nanospheres:
[0035] The bimetallic oxide precursor is placed in a quartz boat and placed in the middle of a tube furnace. The precursor and thiourea are in a mass ratio of 1:3. The thiourea is placed in a quartz boat and placed at the upper air outlet of the tube furnace. After annealing at 2°C / min to 250°C for 2 hours under an inert atmosphere, the temperature is then increased to 650°C at 5°C / min and annealed for 2 hours for sulfurization to obtain a bimetallic sulfide nanosphere structure coated with a carbon layer.
[0036] Step 3: Preparation of Mxene-iron-molybdenum bimetallic sulfide nanosphere composite material:
[0037] 0.2 g of bimetallic sulfide nanospheres coated with carbon layer were mixed with 0.2 g of Mxene (Sinopharm Chemical Reagent Co., Ltd., Ti3C2T X -MXene) was mixed with the mixture in a ball mill for 2 h to obtain a MXene-bimetallic sulfide composite material.
[0038] Comparative Example 1
[0039] Step 1: Preparation of iron-molybdenum bimetallic oxide nanospheres:
[0040] Weigh 2mmol of ferric nitrate and 3mmol of sodium molybdate and dissolve them in 30ml of deionized water respectively, stir them evenly and record them as solution A and solution B respectively; add solution A into solution B while stirring, add 2.5g of polyvinyl pyrrolidone after sufficient stirring, and continue stirring to obtain a mixed solution; transfer the mixed solution into a polytetrafluoroethylene reactor, react at 200°C for 24 hours, cool to room temperature after the reaction is completed, take out the material, wash it with deionized water and ethanol by centrifugation for multiple times, and dry it to obtain an iron-molybdenum bimetallic oxide nanosphere precursor;
[0041] Step 2: Preparation of iron-molybdenum bimetallic sulfide nanospheres:
[0042] The bimetallic oxide precursor was placed in a quartz boat in the middle of a tube furnace. The precursor and thiourea were in a mass ratio of 1:3. The thiourea was placed in a quartz boat at the upper air outlet of the tube furnace. After annealing at 2°C / min to 250°C for 2 hours under an inert atmosphere, the temperature was then increased to 650°C at 5°C / min and annealed for 2 hours for sulfurization to obtain a bimetallic sulfide nanosphere structure coated with a carbon layer, which was recorded as FMSC.
[0043] Application Example 1
[0044] The Mxene-iron-molybdenum bimetallic sulfide@carbon composite material (Mxene-FMSC) prepared in Example 1, the conductive agent SP and the binder PVDF are mixed, then dissolved and mixed evenly to obtain a slurry, and the slurry is evenly coated on the surface of the current collector to obtain a xene-iron-molybdenum bimetallic sulfide@carbon composite material negative electrode sheet.
[0045] The method for preparing the negative electrode sheet in Application Example 1 was used to prepare the corresponding negative electrode sheet using commercial MoS2 (MS) and FMSC prepared in Comparative Example 1. The rate performance was tested at current densities of 0.1, 0.2, 0.5, and 1 A / g, and the cycle performance was tested at a current density of 0.1 A / g. Figure 3 , Figure 4 These are the impedance diagram and cycle performance diagram of the button battery equipped with Mxene-iron-molybdenum bimetallic sulfide@carbon composite material.
[0046] Figure 5 This is the rate performance diagram of commercial MoS2, iron-molybdenum bimetallic sulfide@carbon composite material and Mxene-iron-molybdenum bimetallic sulfide@carbon composite material. The addition of Mxene improves the conductivity and electrode kinetics, and improves the rate performance to a certain extent. At a current density of 0.1A / g, the first cycle specific capacity increases from 540mAh g -1 Increased to 690mAh g -1 At a current density of 1A / g, the discharge capacity is 135mAh g -1 Increased to 188mAh g -1 .
[0047] Example 2
[0048] A Mxene-iron-molybdenum bimetallic sulfide@carbon composite material, the preparation method comprising the following steps:
[0049] Step 1: Preparation of iron-molybdenum bimetallic oxide nanospheres:
[0050] Weigh 2mmol of ferric nitrate and 3mmol of sodium molybdate and dissolve them in 30ml of deionized water respectively, stir them evenly and record them as solution A and solution B respectively; add solution A into solution B while stirring, add 2.5g of polyvinyl pyrrolidone after sufficient stirring, and continue stirring to obtain a mixed solution; transfer the mixed solution into a polytetrafluoroethylene reactor, react at 200°C for 24 hours, cool to room temperature after the reaction is completed, take out the material, wash it with deionized water and ethanol by centrifugation for multiple times, and dry it to obtain an iron-molybdenum bimetallic oxide nanosphere precursor;
[0051] Step 2: Preparation of iron-molybdenum bimetallic sulfide nanospheres:
[0052] The bimetallic oxide precursor is placed in a quartz boat and placed in the middle of a tube furnace. The precursor and thiourea are in a mass ratio of 1:3. The thiourea is placed in a quartz boat and placed at the upper air outlet of the tube furnace. After annealing at 2°C / min to 250°C for 2 hours under an inert atmosphere, the temperature is then increased to 650°C at 5°C / min and annealed for 2 hours for sulfurization to obtain a bimetallic sulfide nanosphere structure coated with a carbon layer.
[0053] Step 3: Preparation of Mxene-iron-molybdenum bimetallic sulfide nanosphere composite material:
[0054] 0.4 g of carbon-coated bimetallic sulfide nanospheres and 0.2 g of Mxene were mixed in a ball mill for 2 h to obtain a Mxene-bimetallic sulfide composite material.
[0055] Figure 2 This is the phase characterization of the bimetallic sulfide material prepared in Example 2. According to the XRD data analysis, it can be seen that the bimetallic sulfide is successfully prepared.
[0056] Example 3
[0057] A Mxene-iron-molybdenum bimetallic sulfide@carbon composite material, the preparation method comprising the following steps:
[0058] Weigh 2mmol of ferric nitrate and 3mmol of sodium molybdate and dissolve them in 30ml of deionized water respectively, stir them evenly and record them as solution A and solution B respectively; add solution A into solution B while stirring, add 4g of polyvinyl pyrrolidone after sufficient stirring, and continue stirring to obtain a mixed solution; transfer the mixed solution into a polytetrafluoroethylene reactor, react at 200°C for 24 hours, cool to room temperature after the reaction is completed, take out the material, wash it several times by centrifugation with deionized water and ethanol, and dry it to obtain an iron-molybdenum bimetallic oxide nanosphere precursor;
[0059] Step 2: Preparation of iron-molybdenum bimetallic sulfide nanospheres:
[0060] The bimetallic oxide precursor is placed in a quartz boat and placed in the middle of a tube furnace. The precursor and thiourea are in a mass ratio of 1:3. The thiourea is placed in a quartz boat and placed at the upper air outlet of the tube furnace. After annealing at 2°C / min to 250°C for 2 hours under an inert atmosphere, the temperature is then increased to 650°C at 5°C / min and annealed for 2 hours for sulfurization to obtain a bimetallic sulfide nanosphere structure coated with a carbon layer.
[0061] Step 3: Preparation of Mxene-iron-molybdenum bimetallic sulfide nanosphere composite material:
[0062] 0.2 g of carbon-coated bimetallic sulfide nanospheres and 0.2 g of Mxene were mixed in a ball mill for 3 h to obtain a Mxene-bimetallic sulfide composite material.
[0063] Figure 1 The morphology of the bimetallic oxides prepared by adding different proportions of polyvinyl pyrrolidone is shown in Figure (a). The material prepared according to the carbon source proportion in Example 1, and Figure (b) is the material prepared according to the carbon source proportion in Example 3. The sample size in Figure (a) is uniform relative to that in Figure (b).
[0064] Example 4
[0065] A Mxene-iron-molybdenum bimetallic sulfide@carbon composite material, the preparation method comprising the following steps:
[0066] Weigh 2mmol of ferric nitrate and 3mmol of sodium molybdate and dissolve them in 30ml of deionized water respectively, stir them evenly and record them as solution A and solution B respectively; add solution A into solution B while stirring, add 4g of polyvinyl pyrrolidone after sufficient stirring, and continue stirring to obtain a mixed solution; transfer the mixed solution into a polytetrafluoroethylene reactor, react at 200°C for 24 hours, cool to room temperature after the reaction is completed, take out the material, wash it several times by centrifugation with deionized water and ethanol, and dry it to obtain an iron-molybdenum bimetallic oxide nanosphere precursor;
[0067] Step 2: Preparation of iron-molybdenum bimetallic sulfide nanospheres:
[0068] The bimetallic oxide precursor is placed in a quartz boat and placed in the middle of a tube furnace. The precursor and thiourea are in a mass ratio of 1:3. The thiourea is placed in a quartz boat and placed at the upper air outlet of the tube furnace. After annealing at 2°C / min to 250°C for 2 hours under an inert atmosphere, the temperature is then increased to 650°C at 5°C / min and annealed for 2 hours for sulfurization to obtain a bimetallic sulfide nanosphere structure coated with a carbon layer.
[0069] Step 3: Preparation of Mxene-iron-molybdenum bimetallic sulfide nanosphere composite material:
[0070] 0.4 g of carbon-coated bimetallic sulfide nanospheres and 0.2 g of Mxene were mixed in a ball mill for 3 h to obtain a Mxene-bimetallic sulfide composite material.
[0071] Example 5
[0072] A Mxene-iron-molybdenum bimetallic sulfide@carbon composite material, the preparation method comprising the following steps:
[0073] Step 1: Preparation of iron-molybdenum bimetallic oxide nanospheres:
[0074] Weigh 2mmol of ferric nitrate and 3mmol of sodium molybdate and dissolve them in 30ml of deionized water respectively, stir them evenly and record them as solution A and solution B respectively; add solution A into solution B while stirring, add 6g of polyvinyl pyrrolidone after sufficient stirring, and continue stirring to obtain a mixed solution; transfer the mixed solution into a polytetrafluoroethylene reactor, react at 200°C for 24 hours, cool to room temperature after the reaction is completed, take out the material, wash it several times by centrifugation with deionized water and ethanol, and dry it to obtain an iron-molybdenum bimetallic oxide nanosphere precursor;
[0075] Step 2: Preparation of iron-molybdenum bimetallic sulfide nanospheres:
[0076] The bimetallic oxide precursor is placed in a quartz boat and placed in the middle of a tube furnace. The precursor and thiourea are in a mass ratio of 1:3. The thiourea is placed in a quartz boat and placed at the upper air outlet of the tube furnace. After annealing at 2°C / min to 250°C for 2 hours under an inert atmosphere, the temperature is then increased to 650°C at 5°C / min and annealed for 2 hours for sulfurization to obtain a bimetallic sulfide nanosphere structure coated with a carbon layer.
[0077] Step 3: Preparation of Mxene-iron-molybdenum bimetallic sulfide nanosphere composite material:
[0078] 0.2 g of carbon-coated bimetallic sulfide nanospheres and 0.2 g of Mxene were mixed in a ball mill for 3 h to obtain a Mxene-bimetallic sulfide composite material.
[0079] Example 6
[0080] A Mxene-iron-molybdenum bimetallic sulfide@carbon composite material, the preparation method comprising the following steps:
[0081] Step 1: Preparation of iron-molybdenum bimetallic oxide nanospheres:
[0082] Weigh 2mmol of ferric nitrate and 3mmol of sodium molybdate and dissolve them in 30ml of deionized water respectively, stir them evenly and record them as solution A and solution B respectively; add solution A into solution B while stirring, add 6g of polyvinyl pyrrolidone after sufficient stirring, and continue stirring to obtain a mixed solution; transfer the mixed solution into a polytetrafluoroethylene reactor, react at 200°C for 24 hours, cool to room temperature after the reaction is completed, take out the material, wash it several times by centrifugation with deionized water and ethanol, and dry it to obtain an iron-molybdenum bimetallic oxide nanosphere precursor;
[0083] Step 2: Preparation of iron-molybdenum bimetallic sulfide nanospheres:
[0084] The bimetallic oxide precursor is placed in a quartz boat and placed in the middle of a tube furnace. The precursor and thiourea are in a mass ratio of 1:3. The thiourea is placed in a quartz boat and placed at the upper air outlet of the tube furnace. After annealing at 2°C / min to 250°C for 2 hours under an inert atmosphere, the temperature is then increased to 650°C at 5°C / min and annealed for 2 hours for sulfurization to obtain a bimetallic sulfide nanosphere structure coated with a carbon layer.
[0085] Step 3: Preparation of Mxene-iron-molybdenum bimetallic sulfide nanosphere composite material:
[0086] 0.4 g of carbon-coated bimetallic sulfide nanospheres and 0.2 g of Mxene were mixed in a ball mill for 3 h to obtain a Mxene-bimetallic sulfide composite material.
[0087] Example 7
[0088] A Mxene-iron-molybdenum bimetallic sulfide@carbon composite material, the preparation method comprising the following steps:
[0089] Step 1: Preparation of iron-molybdenum bimetallic oxide nanospheres:
[0090] Weigh 3mmol of ferric chloride and 3mmol of ammonium molybdate and dissolve them in 150ml of deionized water respectively, stir them evenly and record them as solution A and solution B respectively; add solution A into solution B while stirring, add 3g of polydopamine after sufficient stirring, and continue stirring to obtain a mixed solution; transfer the mixed solution into a polytetrafluoroethylene reactor, react at 160°C for 16 hours, cool to room temperature after the reaction is completed, take out the material, wash it several times by centrifugation with deionized water and ethanol, and dry it to obtain an iron-molybdenum bimetallic oxide nanosphere precursor;
[0091] Step 2: Preparation of iron-molybdenum bimetallic sulfide nanospheres:
[0092] The bimetallic oxide precursor is placed in a quartz boat and placed in the middle of a tube furnace. The precursor and thioacetamide are in a mass ratio of 1:100. Thioacetamide is placed in a quartz boat and placed on the upper air outlet of the tube furnace. The temperature is increased to 200°C at 2°C / min under an inert atmosphere and annealed for 1 hour. The temperature is then increased to 700°C at 5°C / min and annealed for 1 hour for sulfurization to obtain a bimetallic sulfide nanosphere structure coated with a carbon layer.
[0093] Step 3: Preparation of Mxene-iron-molybdenum bimetallic sulfide nanosphere composite material:
[0094] 0.3 g of carbon-coated bimetallic sulfide nanospheres and 0.2 g of Mxene were mixed in a ball mill for 1 h to obtain a Mxene-bimetallic sulfide composite material.
[0095] Example 8
[0096] A Mxene-iron-molybdenum bimetallic sulfide@carbon composite material, the preparation method comprising the following steps:
[0097] Step 1: Preparation of iron-molybdenum bimetallic oxide nanospheres:
[0098] Weigh 3mmol of ferric nitrate and 1mmol of sodium molybdate and dissolve them in 5ml of deionized water respectively, stir them evenly and record them as solution A and solution B respectively; add solution A into solution B while stirring, add 5g of polydopamine after sufficient stirring, and continue stirring to obtain a mixed solution; transfer the mixed solution into a polytetrafluoroethylene reactor, react at 240°C for 12 hours, cool to room temperature after the reaction is completed, take out the material, wash it several times by centrifugation with deionized water and ethanol, and dry it to obtain an iron-molybdenum bimetallic oxide nanosphere precursor;
[0099] Step 2: Preparation of iron-molybdenum bimetallic sulfide nanospheres:
[0100] The bimetallic oxide precursor is placed in a quartz boat and placed in the middle of a tube furnace. The precursor and sublimated sulfur are in a mass ratio of 100:1. The sublimated sulfur is placed in a quartz boat and placed at the upwind side of the tube furnace. The temperature is increased to 300°C at 2°C / min and annealed for 3 hours under an inert atmosphere. The temperature is then increased to 500°C at 5°C / min and annealed for 3 hours for sulfurization to obtain a bimetallic sulfide nanosphere structure coated with a carbon layer.
[0101] Step 3: Preparation of Mxene-iron-molybdenum bimetallic sulfide nanosphere composite material:
[0102] 0.4 g of carbon-coated bimetallic sulfide nanospheres and 0.2 g of Mxene were mixed in a ball mill for 5 h to obtain a Mxene-bimetallic sulfide composite material.
[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a Mxene-iron-molybdenum bimetallic sulfide@carbon composite material, characterized in that: The following steps are involved: (1) dissolving an iron source, a molybdenum source and a carbon source in a solvent to prepare a mixed solution, and then performing a hydrothermal reaction to obtain bimetallic oxide nanospheres; (2) subjecting the bimetallic oxide nanospheres to high temperature sulfurization to obtain iron-molybdenum bimetallic sulfide@carbon; (3) Mxene and iron-molybdenum bimetallic sulfide@carbon are mixed by ball milling to prepare Mxene-iron-molybdenum bimetallic sulfide@carbon composite material.
2. The method for preparing the Mxene-iron-molybdenum bimetallic sulfide@carbon composite material according to claim 1, characterized in that: The iron source is ferric chloride and / or ferric nitrate; the molybdenum source is one or more of sodium molybdate, ammonium molybdate or ammonium heptamolybdate.
3. The method for preparing the Mxene-iron-molybdenum bimetallic sulfide@carbon composite material according to claim 1, characterized in that: The carbon source is polyvinyl pyrrolidone or polydopamine, the concentration of the carbon source in the mixed solution is 0.01-0.5 g / ml, and the solvent is water.
4. The method for preparing the Mxene-iron-molybdenum bimetallic sulfide@carbon composite material according to claim 3, characterized in that: The molar ratio of the iron source to the molybdenum source is (1-3): (1-3), and the concentration of the molybdenum source in the mixed solution is 0.01-0.1 mmol / ml.
5. The method for preparing the Mxene-iron-molybdenum bimetallic sulfide@carbon composite material according to any one of claims 1 to 3, characterized in that: The conditions of the hydrothermal reaction are: temperature 160-240° C., time 12-24 h.
6. The method for preparing the Mxene-iron-molybdenum bimetallic sulfide@carbon composite material according to claim 5, characterized in that: The sulfur source used in the high-temperature vulcanization treatment is one or more of sublimated sulfur, thiourea or thioacetamide; the mass ratio of the bimetallic oxide nanospheres to the sulfur source is (0.01-1): (0.01-1).
7. The method for preparing the Mxene-iron-molybdenum bimetallic sulfide@carbon composite material according to claim 6, characterized in that: The temperature of the high temperature vulcanization treatment is 200-700° C. and the time is 2-6 hours.
8. The method for preparing the Mxene-iron-molybdenum bimetallic sulfide@carbon composite material according to claim 7, characterized in that: The mass ratio of the Mxene to the iron-molybdenum bimetallic sulfide@carbon is 1:(1-2).
9. The Mxene-iron-molybdenum bimetallic sulfide@carbon composite material prepared by the method according to any one of claims 1 to 8.
10. The Mxene-iron-molybdenum bimetallic sulfide@carbon composite material according to claim 9 is used as a negative electrode material for a sodium ion battery.
Citation Information
Cited By
Nano composite material with heterogeneous hollow multi-shell structure as well as preparation method and application of nano composite material
CN119650668A
A heterogeneous hollow multi-shell structure nanocomposite and a preparation method and application thereof
CN119650668B
Composite negative electrode material and preparation method thereof, negative electrode plate, battery and electronic device
CN119812281A